2021
DOI: 10.21037/atm-21-1705
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1: is it related to the stiffness of breast lesions and can it predict axillary lymph node metastasis?

Abstract: Background: This study aimed to explore whether transforming growth factor β1 (TGF-β1) is correlated with the stiffness of breast lesions and if it can predict axillary lymph node (ALN) metastasis.Methods: A retrospective analysis was performed in our hospital. A total of 135 breast lesions in 130 patients who were to undergo vacuum-assisted excisional biopsy (VAEB) or surgery were enrolled between April 2018 and October 2018. Ultrasound (US) and shear wave elastography (SWE) examinations were performed for ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Fig 5. The expression level of COL1A1 was positively correlated with Emax(A), Emean(B), Eratio(C), (r = 0.406, 0.362, 0.425, respectively.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Fig 5. The expression level of COL1A1 was positively correlated with Emax(A), Emean(B), Eratio(C), (r = 0.406, 0.362, 0.425, respectively.…”
mentioning
confidence: 88%
“…The advent of shear wave elastography (SWE) offers the possibility of achieving quantitative judgment of tissue stiffness and can facilitate appropriate degradation of masses with low suspicion of breast imaging reporting and data system (BI-RADS) category 4A at soft borders [2]. Recently, several studies have reported that SWE showed good performance in assessing benign and malignant lesions [3][4][5]. The stromal reaction that occurs because of invasive behavior results in abnormal tumor-associated collagen deposition, potentially leading to increased elastic modulus values in breast cancer [6].…”
Section: Introductionmentioning
confidence: 99%